PENDUGAAN ELASTISITAS PENAWARAN OUTPUT DAN PERMINTAAN INPUT USAHATANI JAGUNG - Agustian, Adang; Hartoyo, Sri (Universitas Muhammdaiyah Surakarta, 2012)
This study aims to determine the effect of changes in output and input prices, corn research expenditures and road infrastructure on output supply and input demand for corn in the Province of East Java and West Java. The data that are analyzed are those of structure of costs of corn farming in the Province of East Java and West Java in 1985-2009. Estimation model employed is the method of Seemingly Unrelated Regression. The results showed that the output supply of corn both in the province of East Java and West Java are elastic to its price changes, however it is inelastic to the price changes of: seed, urea, TSP and labor. Input demand of seed, urea, TSP and labor area inelastic to their price changes. Policy implications of this research is efforts to increase the supply of corn can be carried out by increasing its price, expenditures of corn research, and road infrastructure.